2016
DOI: 10.2337/dc16-0610
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Injection Into Lipohypertrophic Tissue: Blunted and More Variable Insulin Absorption and Action and Impaired Postprandial Glucose Control

Abstract: Insulin absorption and action are blunted and considerably more variable with LHT injection, leading to profound deterioration in postprandial glucose control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
115
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(128 citation statements)
references
References 22 publications
4
115
0
9
Order By: Relevance
“…Injecting into areas of LH reduces insulin absorption and also raises within-subject uptake variability with a coefficient of variability (CV%) that is three- to fivefold higher than when injecting into normal tissue; therefore, this practice must be avoided [24]. Clearly there is much more that can be done to raise awareness of LH as well as intervene by teaching proper site rotation and limiting needle reuse [25].…”
Section: Discussionmentioning
confidence: 99%
“…Injecting into areas of LH reduces insulin absorption and also raises within-subject uptake variability with a coefficient of variability (CV%) that is three- to fivefold higher than when injecting into normal tissue; therefore, this practice must be avoided [24]. Clearly there is much more that can be done to raise awareness of LH as well as intervene by teaching proper site rotation and limiting needle reuse [25].…”
Section: Discussionmentioning
confidence: 99%
“…Case reports indicate that clinical palpation has also failed to detect lipohypertrophy with improvement in glycaemic indices once identified by ultrasonography . With accumulating evidence of altered insulin absorption dynamics at known sites of clinical lipohypertrophy , dedicated studies are required to determine if subclinical lesions such as those characterized in the present study also contribute to glycaemic variability. No difference was noted in overall glycaemic control, as measured by HbA 1c , between subgroups of participants with clinical, subclinical or absent lipohypertrophy; however, the necessary power to detect potential differences was not factored into the initial study design (data not shown).…”
Section: Discussionmentioning
confidence: 80%
“…The main reasons could be impaired and variable insulin absorption and action when the insulin is injected into the affected tissue. [40] Frid et al . have documented significantly higher occurrence of unexpected hypoglycemia and glucose variability in patients who had LH and incorrect rotation of site.…”
Section: Discussionmentioning
confidence: 99%